2013
DOI: 10.1590/s0101-20612013005000007
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value and fatty acid composition of some traditional Argentinean meat sausages

Abstract: The aim of this study was to determine the nutritional composition (moisture, protein, carbohydrates, and total fat) of some meat products produced in the northeastern Argentina, analyzing fatty acids composition, polyunsaturated/saturated fatty acid ratio PUFA/SFA ratio (polyunsaturated/ saturated fatty acids), n-6/n-3 ratio, and CLA (conjugated linoleic acid) content. Thirty traditional meat products produced by different processes were used. The samples were classified into 4 different categories as follows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 17 publications
7
27
0
5
Order By: Relevance
“…Amaral et al [40] showed that pork Frankfurter type sausages contained from 45.29% to 51.53% of MUFAs and from 12.21% to 16.54% of PUFAs. Similarly, the average concentration of MUFAs was 44.89% and 11.79% of PUFAs in Chorizo ahumado (smoked sausage) [41].…”
Section: Sausagesmentioning
confidence: 88%
“…Amaral et al [40] showed that pork Frankfurter type sausages contained from 45.29% to 51.53% of MUFAs and from 12.21% to 16.54% of PUFAs. Similarly, the average concentration of MUFAs was 44.89% and 11.79% of PUFAs in Chorizo ahumado (smoked sausage) [41].…”
Section: Sausagesmentioning
confidence: 88%
“…All sausages produced like the rest of the Western fermented sausages had an excessively high ratio, which was around 10-11/1 due to the extremely low content of n-3 fatty acids (EPA, DHA) (Valencia et al, 2006); thus, they contributed little in terms of dietary recommendations (Romero et al, 2013). Increases in SFA were observed (p ≤ 0.05) in all samples (~ 10 %), except in the sample with sea salt only (S), in which SFA was constant for all the storage period.…”
Section: Composition Of Fatty Acidmentioning
confidence: 99%
“…SFA are considered to raise plasma cholesterol, except for stearic acid which reduces total and LDL cholesterol and the MUFA have a hypocholesterolemic effect, but they do not decrease HDL cholesterol, which protects against cardiovascular diseases (Romero et al, 2013). Thus, the PUFA/SFA-C18:0 ratio and MUFA+PUFA/SFA-C18:0 ratio (Romero et al, 2013) were calculated for sausage and are shown in Table 1.…”
Section: Analysis Of Conjugated Dienes and Tbars Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Os resultados de pH (6,6 ± 0,07) e atividade de água (0,9 ± 0,00) do queijo de porco estão próximos aos descritos para outros produtos cárneos cozidos (ROMERO et al, 2013 (CACHALDORA et al, 2013). Mesmo com o uso do corante carmim de colchonilha (a* = 10,5) na formulação, o produto estudado apresentou baixo índice de vermelho, provavelmente pela interação do nitrito oxidando a mioglobina a metamioglobina ou pelo cozimento causando a desnaturação das proteínas do grupo heme (HONIKEL, 2008).…”
Section: Resultsunclassified